Distributed generator control mode and its effect on the dynamic behaviour of a distribution network - Azizan A.W.; Ramachandaramurthy V.K.; Loo C.K. (2023)
A synchronous distributed generator (DG) power generation is controlled at specific modes, defined as Voltage control mode (PV) and power factor control mode (PQ), to demonstrate an electrical network dynamic behaviour as a result of DG connection to the system. PSCAD/EMTDC software is used to model and simulate the network. The results show the network profiles correspond to the different amounts of DG power generated.